THE ROLE OF THE ORGANIC FERTILIZER PROCESSING UNIT (UPPO) ON RICE FARMERS' INCOME IN DELI SERDANG DISTRICT - Andalasari, Rina; Lubis, Yusniar; Kardhinata, Harso (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
In efforts to minimize the use of inorganic fertilizers and support farmers in using and supplying organic fertilizers independently, the government facilitates providing assistance in the form of Organic Fertilizer Processing Units (UPPO). It is hoped that the availability of organic fertilizers can lead to organic farming. This study aims to determine the role of UPPO on the income of lowland rice farmers in Deli Serdang district and to analyze other factors besides UPPO that affect farmers' income. This research was conducted on eight beneficiary farmer groups spread over seven sub-districts in Deli Serdang district with a total population of 70 farmers. The research method uses analysis of validity and reliability tests, classical assumption tests, and regression analysis. The results showed that all research variables separately had a significant effect on farmers' income.